Rejuvenation of Constitutional Ethics in the Sapta Karsa Hutama of the Constitutional Court - Bramasta, Bima; Yazwardi, Yazwardi; Holijah, Holijah (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study originates from the constitutional ethics crisis in Indonesian constitutional practice, highlighted by ethical violations committed by constitutional judges. Such cases raise doubts about the effectiveness of Sapta Karsa Hutama as an ethical guideline and moral foundation for the Constitutional Court. The study aims to analyze the relevance of Sapta Karsa Hutama in rejuvenating constitutional ethics and strengthening the Court’s role as the guardian of the constitution and democracy. A normative legal method was applied using conceptual, historical, and statutory approaches, supported by academic literature. The findings reveal that Sapta Karsa Hutama is urgent as an ethical instrument emphasizing integrity, justice, responsibility, and accountability. Weak enforcement, limited internalization of values, and a fragile legal culture have hindered its implementation. The study concludes that rejuvenating constitutional ethics through Sapta Karsa Hutama is essential to uphold the Court’s dignity. It recommends strengthening ethical education, establishing independent oversight mechanisms, and integrating ethical values into constitutional practice to ensure that the rule of ethics operates alongside the rule of law. [Penelitian ini berangkat dari krisis etika konstitusi dalam praktik ketatanegaraan Indonesia yang mencuat melalui kasus pelanggaran kode etik hakim konstitusi. Kondisi ini menimbulkan keraguan terhadap efektivitas Sapta Karsa Hutama sebagai pedoman etik dan dasar moral Mahkamah Konstitusi. Tujuan penelitian adalah menganalisis relevansi Sapta Karsa Hutama dalam merejuvenasi etika konstitusi dan memperkuat peran Mahkamah Konstitusi sebagai penjaga konstitusi dan demokrasi. Penelitian menggunakan metode hukum normatif dengan pendekatan konseptual, historis, dan perundang-undangan, didukung kajian literatur akademik. Hasil menunjukkan bahwa Sapta Karsa Hutama memiliki urgensi sebagai instrumen etik yang menekankan integritas, keadilan, tanggung jawab, dan akuntabilitas. Lemahnya implementasi selama ini disebabkan inkonsistensi penegakan, minimnya internalisasi nilai, serta lemahnya budaya hukum. Kesimpulannya, rejuvenasi etika konstitusi melalui Sapta Karsa Hutama penting untuk menjaga martabat Mahkamah Konstitusi. Penelitian merekomendasikan penguatan pendidikan etik, mekanisme pengawasan yang independen, dan integrasi nilai etika dalam praktik ketatanegaraan agar rule of ethics berjalan seiring dengan rule of law.]